Benign and Malignant Breast Disease in South Wales: A Study of Urinary Steroids. Issue 5738 (26th December 1970) - Cameron, E. H. D.; Griffiths, K.; Gleave, E. N.; Stewart, H. J.; Forrest, A. P. M.; Campbell, H.
Abstract : The levels of aetiocholanolone, androsterone, and 17-hydroxycorticosteroids were measured in women without known disease of the breast, in women with benign breast disease, and in women with primary and advanced breast cancer. Statistical analysis showed there was no difference in the excretion of urinary 17-hydroxycorticosteroids in the various groups of patients. Detailed analysis of the aetiocholanolone and androsterone levels, however, indicated that patients with advanced localized disease excreted significantly less of these 11-deoxy-17-oxosteroids than those in the other groups.